(untitled) (Research, Society and Development, 2020)
Objective: To assess the occurrence of falls in patients admitted to a tertiary hospital in northeastern Brazil. Methods: An observational, retrospective study with a quantitative approach was conducted, developed in a tertiary hospital in northeastern Brazil, with patients admitted to the clinical, surgical, oncology, pediatric and Intensive Care Units. A fall audit form were used for data collection and The London Protocol. To validate the statistical differences between the care units, the Fisher-Freeman-Halton test was used. Results: It was found that out of the 136 evaluated patients who suffered a fall, they were predominantly male, elderly, married, assessed as high risk for the event according to the protocols, the majority of which occurred in the morning, from their own height and in the room with the presence of family members. Conclusion: Patients were assessed as being at high risk for the event, despite having preventive measures, these did not prevent the occurrence of falls. The scenario reinforces the importance of surveillance, health education and care to reduce the risk of falls and possible injuries.